PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PT. 24 JAM ONLINE) - Francesco Satria Yudhistira Huring , Anita Silvianita (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2018)
This research was conducted at PT. 24 Jam Online which they are the popular company that give a paymet service for virtual game online include computer game or mobile game in Indonesia This research was conducted to determine the influence of stress work and work environment on employee performance (study on PT. 24 Jam Online employee). The method used is the quantitative methods with this type of research is a study of the causal and descriptive. The sampling that used in this research is probability sampling with the type nonprobability sampling. The number of respondents are 46 employees in PT. 24 Jam Online. Data analysis technique that being used is multiple linear regression analysis. In this research shows that work stress on high category, environment work on high category and the employee performance on high category. Based on the coefficient of determination is obtained that the influence stress work variables (X1) and environment work (X2) on the employee performance (Y) is 86,4%. And the remaining is 30,8 % of rest is affected by other factors that were not examined in this research. Keywords: Work Stress, Environment Work, Employee Performance, PT. 24 Jam Online